Pengaruh Pemberian Ekstrak Etanol Buah Makasar (Brucea javanica [L.] Merr) terhadap Aktivitas dan Kapasitas Fagositosis serta Produksi ROI Sel Fagosit Mencit secara In vivo - ROS SUMARNY; SILVI RISDIYANTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
One way to prevent of disease through increased endurance by increasing the effectiveness of the immune system to light the causes of disease. Macassar fruit (Brucea javanica [L.] Merr) of Simambaceae is known containing quasinoid which has cytotoxic activity against cancer, antiplasmodium, and improving the effectiveness of humoral immun system. The work is to investigate the effect of Macassar fruit ethanol extract on the activity and phagocytic capacity, as well as phagocyte ROI production of mice phagocyte cells. Five groups consisted of 12 mice per group were prepared. Group I, a normal control was given distilled water, Group II was given orally with Macassar fruit ethanol extract dose of 100 mg/ kg, Group III a dose of 200 mg/kg, Group IV a dose of 300 mg/kg, and positive control group V was given Stimuno. Results showed that the phagocytic activity of phagocyte cells increased with increasing doses. The highest phagocytic activity was achieved by the 300 mg/kg dose, observed either at 8th and 15th days after the treatment, with an increase in phagocytic activity of 65 .60% and 70.5%. ROI production of phagocytic cells has different response after 7 days or 14 days treatment with Macassar fruit extract. The ROI production increased by 43% after 14 days treatment with Maccasar fruit ethanol extract with the dose of 300 mg/kg BW.